Dualizem telesa in duše - Hudej, Franc (Teorija in praksa, 2013)
The dualism of body and soul is present in theology and the sacred books of most religions, as well as in philosophical and psychological works. Descartes realised that the body is composed of matter, the soul is not the body and that ultimately the soul is infinite. Spinoza opposed Descartes' idea of the dualism of soul and body. He realised that matter is behind all the features of infinity, indeterminacy and going so everything reveals its origins in matter. The latest research in the field of the live cell genome and the brain do not support the dualism of body and soul. The body is not only what we see and touch and the soul is not a separate entity but an integral part of the process in the neural network. Damasio notes that the human body is a complex and integrated whole with a brain that is constantly changing. Modern neuroscience recognises that all human mental activities attributable to the soul arise from the brain and that the brain and body form a single organism.
Keywords: Človekovo telo; Dualism; Dualizem; Duša; Human body; možgani; Neurosciences; Nevroznanosti; Soul; zavest